2008
DOI: 10.1186/1471-2458-8-193
|View full text |Cite
|
Sign up to set email alerts
|

Association between television viewing and the risk of metabolic syndrome in a community-based population

Abstract: Background: As a result of metabolic syndrome becoming an important issue during recent decades, many studies have explored the risk factors contributing to its development. However, less attention has been paid to the risk associated with sedentary behavior, especially television viewing. This study examined the association between television viewing time and the risk of having metabolic syndrome in a population of Taiwanese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 43 publications
5
50
0
5
Order By: Relevance
“…A sizeable body of cross-sectional and prospective evidence suggests that sedentary behavior and physical activity are independently associated with BMI in adults. [20][21][22][23][24] In fact, research has found relatively low correlations between time spent in physical activity and sedentary behavior. 24,25 However, it is unclear whether the strength of the association between sedentary behavior and BMI varies according to time spent in physical activity, or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…A sizeable body of cross-sectional and prospective evidence suggests that sedentary behavior and physical activity are independently associated with BMI in adults. [20][21][22][23][24] In fact, research has found relatively low correlations between time spent in physical activity and sedentary behavior. 24,25 However, it is unclear whether the strength of the association between sedentary behavior and BMI varies according to time spent in physical activity, or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the findings of the current study may be limited by the use of the specific thresholds to summarize accelerometer. However, the threshold of 100 cpm to define sedentary behaviour has been previously proposed by Treuth et al [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In both genders high PAL has been associated with reduced adiposity/plasma lipid profile 5,18 , and TV viewing with increased metabolic risk factors 5,6 . When numerical variables are analyzed, the information from our study agreed with these previous data, where highest BMI values were observed in men grouped in lowest frequency group for walking and cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Television viewing (TV viewing) is an important indicator of physical inactivity, because the number of television sets per person increased following the overweight trend 4 and frequently it is associated with adiposity and metabolic risks during adulthood 5,6 . A conceptual model to explain the association between sedentary behavior and cardiovascular risk factors could be the decreased physical activity level (PAL) which would be associated with increased time spent in sedentary behavior, such as TV viewing.…”
mentioning
confidence: 99%